Bioavailability Enhancement of Silybin Through Carbon-23 Acid Derivatization - Amin1, Lena Nawzad; Sabir, Mohammed N.; Al-Khafaji, Emad Manhal; Rachid, Shwan (Sulaimani Journal for Pure and Applied Sciences, 2015)
Silybin is an isomer derived from the seed of Silybum marianum, a biennial metropolitan plant that is grown naturally in Iraqi Kurdistan Region, it shows antioxidant and anticancer activity however; its poor water solubility encounters to low bioavailability which limits its use in clinical practice. To improve water solubility thereby bioavailability, a chemical derivatization (carboxylic acid) on C-23 (C27H24O12) was performed. Silybin derivative on C-23 as ether function improves solubility through increasing the ability to donate unshared electron pairs like Lewis base. The elongated carbon chain 25 as carboxylic acid increases the polarity of our derivative in water as well as the acidity. Our derivative was prepared by Williamson method and showed improvement of water solubility in comparison to silybin; this will lead to enhance the bioavailability and consequently the activity of the drug. Structure elucidation confirmed by FTIR, 13C-NMR and mass spectroscopy. The solubility assessment was performed according to Beer’s-Lambert law. Aim: Enhance water solubility and bioavailability of silybin through acid derivatization.
Keywords: Silybin; Solubility; Chemical derivatization; Massspectroscopy; Bioavailability